Key Issues Of Word Learning (Eurasian Research Bulletin, 2022)
The article is about the word learning and the peculiarities of Uzbek language in linguistics. The relation Uzbek language with other languages the influence of other languages on the Uzbek language as a result of these relations, mainly in the languages of neighboring peoples, which have direct economic, cultural and political ties with the Uzbek people.